NUMERICAL MODELING OF HEAT TRANSFER OF STEEL TUBE DURING QUENCHING PROCESS - Apipe, Pedro Henrique Vasconcellos; Silva, Ricardo Junqueira; Soares, Lis; Porto, Matheus Pereira; Machado, Luiz (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The evolution of the cooling curve during steel hardening process is essential to define the mechanical properties and quality of the final material. As these properties vary considerably depending on the cooling rate it is essential to monitor and control the temperature evolution in the metal. This paper presents the development of a mathematical modeling of heat transfer, whose purpose is to generate the temporal evolution of the temperature in a quenching process of steel tube in which water is used as cooling fluid. In this modeling the tube is divided into N control volumes. The heat conduction equation is applied to each control volume and conductive heat transfer rate at the tube surface is considered equal heat transfer rate between the tube and water by convection. The model equations are solved by implicit finite volume method. Comparisons between the cooling curves generated by the model are compared with the corresponding curves obtained experimentally in the industrial process. The results show that the model reproduces well the trend of the cooling curve during the process. The results also showed that the cooling curve obtained with the model is very sensitive to convection heat transfer values between the tube and water.